Interpersonal meaning breadth variation in simultaneous interpreting English – bahasa Indonesia dienic texts: A contrastive-translational mood grammar analysis - Christiani, Intan (LingTera, 2020)
This study presents a contrastive-translational MOOD grammar analysis of the realization of interpersonal meaning in Joyce Meyer's English sermon text and Jose Carol's Bahasa Indonesia interpreted text. Interpersonal meaning in the framework of Systemic Functional Linguistics (SFL), the model of Translational Semiotic Communication (TSC) and the model of text type and language function are the theoretical foundations of this study. This study used a descriptive qualitative-quantitative approach, involving the analysis of MOOD and Modality of the data which were translationally related semantic units grammatically expressed by MOOD clause units. The analysis reveals that the texts in this study can be classified as dienic texts with Declaratives and Imperatives as the prominent clauses, while Modality elements realized in T1 were generally realized in T2 in the same types. Declaratives and Imperatives respectively serve the informative and operative function of the texts, and the Modality elements which are mostly of a high degree and expressed explicitly give values to these functions.